Bidang Garapan Kurikulum dalam Administrasi Pendidikan - Nurul Handini; Annida Azhari Ritonga; Namira Sazkia (Universitas Maritim AMNI Semarang, 2024)
The field of curriculum work in educational administration, which is an important process for achieving learning goals. In this field, the preparation of syllabi, lesson plans, semester programs and annual programs is the main focus. It is important to consider factors such as student abilities, resources, and community needs. Elements and areas of educational administration include organization, management, communication, governance/administration, personnel/personnel, financial/financial, facilities and public relations. Analysis of curriculum areas plays an important role in achieving educational goals. Several articles also discuss aspects of curriculum management and educational administration in schools, with a focus on the implementation of curriculum management in certain secondary schools, the role of technology in improving the quality of education, and the scope of educational management in Islamic schools.